Optimasi dan Reinisiasi Sistematis Pembelajaran Elektronik - Vijaya, Annas (Department of Informatics Engineering, 2018)
One of the IT applications implemented in higher education and quite rich in renewable IT features is e-learning. However, facts show that in Indonesia it appears that there are not many universities are moved to apply e-learning, in addition, from the other side for others who have implemented e-learning still leads to a pattern that has not been systematic according to its allocation.This paper will discuss the optimization and re-initiation of e-learning using a case study. In addition to reviewing the aspects of human resources involved in e-learning, the following features and functions can be developed in e-learning, such as collaboration, social networking, and so forth. This review is conducted considering that in addition to e-learning included in the top 10 topics in higher education, e-learning also has the potential as acceleration in the learning process and collaboration on campus..